Expresión yv(x⇔z)
El profesor se sorprenderá mucho al ver tu solución correcta😉
Solución
Solución detallada
x⇔z=(x∧z)∨(¬x∧¬z)y∨(x⇔z)=y∨(x∧z)∨(¬x∧¬z)
y∨(x∧z)∨(¬x∧¬z)
Tabla de verdad
+---+---+---+--------+
| x | y | z | result |
+===+===+===+========+
| 0 | 0 | 0 | 1 |
+---+---+---+--------+
| 0 | 0 | 1 | 0 |
+---+---+---+--------+
| 0 | 1 | 0 | 1 |
+---+---+---+--------+
| 0 | 1 | 1 | 1 |
+---+---+---+--------+
| 1 | 0 | 0 | 0 |
+---+---+---+--------+
| 1 | 0 | 1 | 1 |
+---+---+---+--------+
| 1 | 1 | 0 | 1 |
+---+---+---+--------+
| 1 | 1 | 1 | 1 |
+---+---+---+--------+
y∨(x∧z)∨(¬x∧¬z)
(x∨y∨¬x)∧(x∨y∨¬z)∧(y∨z∨¬x)∧(y∨z∨¬z)
(x∨y∨(¬x))∧(x∨y∨(¬z))∧(y∨z∨(¬x))∧(y∨z∨(¬z))
Ya está reducido a FND
y∨(x∧z)∨(¬x∧¬z)
(x∨y∨¬z)∧(y∨z∨¬x)